2010
DOI: 10.2165/11319020-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Adverse Effects Associated with Systemic Retinoid Dermatotherapy

Abstract: Although neuromuscular adverse effects represent significant clinical manifestations of hypervitaminosis A syndrome, surprisingly little attention has been paid to the potential neuromuscular toxicity of vitamin A derivatives (retinoids). Since isotretinoin and acitretin are currently the two most commonly used oral retinoids in systemic dermatotherapy, this review focuses exclusively on their neuromuscular adverse effects and proposes a neuromuscular algorithm for appropriate monitoring of patients treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 58 publications
1
45
0
2
Order By: Relevance
“…Previous reports have suggested a causal association between oral isotretinoin and acquired central nervous system (CNS) neurotoxicity and neuropathy [57]. The most frequent CNS adverse effect associated with oral isotretinoin is headache, either as an independent adverse effect or as part of benign intracranial hypertension, which is additionally characterized by nausea and visual changes [57].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have suggested a causal association between oral isotretinoin and acquired central nervous system (CNS) neurotoxicity and neuropathy [57]. The most frequent CNS adverse effect associated with oral isotretinoin is headache, either as an independent adverse effect or as part of benign intracranial hypertension, which is additionally characterized by nausea and visual changes [57].…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent CNS adverse effect associated with oral isotretinoin is headache, either as an independent adverse effect or as part of benign intracranial hypertension, which is additionally characterized by nausea and visual changes [57]. A single case of optic swelling associated with isotretinoin has also been reported [8].…”
Section: Introductionmentioning
confidence: 99%
“…Among the many adverse effects of isotretinoin, eye dryness, corneal and retinal abnormalities, myalgia, true myopathy, psychiatric problems, and several autoimmune disorders have been described [2, 3, 4, 5, 6, 7, 8]. A literature review has revealed very few case reports of autoimmune disorders associated with isotretinoin intake.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it is important to note that there also are well-known adverse effects of using retinoids in humans. The two most commonly prescribed oral retinoids, isotretinoin and acitretin, are associated with generalized muscle stiffness syndrome and myalgia in some individuals [93]. Other adverse effects of oral retinoids include dryness of mucous membranes and eyes, increase in serum triglycerides and teratogenicity [94].…”
Section: Resultsmentioning
confidence: 99%